Sequence Variations Within HLA-G and HLA-F Genomic Segments at the Human Leukocyte Antigen Telomeric End Associated With Acute Graft-Versus-Host Disease in Unrelated Bone Marrow Transplantation - Suzuki, Shingo; Morishima, Satoko; Murata, Makoto; Tanaka, Masafumi; Shigenari, Atsuko; Ito, Sayaka; Kanga, Uma; Kulski, Jerzy K.; Morishima, Yasuo; Shiina, Takashi (Frontiers in Immunology, 2022)
Acute graft-versus-host disease (aGVHD) is defined as a syndrome of an immunological response of graft to the host that occurs early after allogeneic hematopoietic stem cell transplantation (HCT). This disease is frequently observed even in HCT matched for Human Leukocyte Antigen (HLA) alleles at multiple gene loci. Although HLA region represents complex and diverse genomic characteristics, detailed association analysis is required for identification of uncharacterized variants that are strongly associated with aGVHD. We genotyped three loci, OR2H2, HLA-F-AS1 and HLA-G, that are located in the 460 kb of HLA telomeric region, and statistically analyzed the genotypes including HLA-DPB1 with clinical and transplantation outcome using 338 unrelated bone marrow transplantation (UR-BMT) patient-donor pairs who were matched for HLA-A, HLA-B, HLA-C, HLA-DRB1 and HLA-DQB1 (HLA-10/10). Multivariate analyses demonstrated that HLA-F-AS1 and HLA-DPB1 mismatches were associated with grade II-IV aGVHD (hazard ratio (HR), 1.76; 95% confidence interval (Cl), 1.07-2.88; P = 0.026 and HR, 1.59; Cl, 1.02-2.49; P = 0.042, respectively). There was no confounding between HLA-F-AS1 and HLA-DPB1 (P = 0.512), suggesting that the HLA-F-AS1 mismatch has a strong effect with aGVHD independently of HLA-DPB1. Moreover, a stratified analysis suggested possible associations of HLA-F-AS1, HLA-DPB1, and/or HLA-G mismatches with grade II-IV aGVHD and the more severe grade III-IV aGVHD. These findings provide new insights into understanding the molecular mechanism of aGVHD caused by HLA-matched UR-BMT.